Antagonisme Trichoderma sp. terhadap Colletotrichum capsici: Uji In Vitro sebagai Strategi Pengendalian Hayati Penyakit Antraknosa pada Cabai Rawit - Triska Wahyuni Dawit; Ani M. Hasan; Jusna Ahmad; Yuliana Retnowati; Febriyanti Febriyanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Anthracnose disease is a plant disease caused by the fungus Colletotrichum capsici, the disease is one of the problems in the cultivation of cayenne pepper (Capsicum frutescens). This study aims to test the antagonistic ability of Trichoderma sp. against the fungus Colletotrichum capsici and observe the morphological changes in Colletotrichum capsici colonies exposed to Trichoderma sp in vitro on cayenne pepper plants Capsicum frutescens. The test method was carried out using the dual culture method to determine the percentage of inhibition by studying the interaction between Trichoderma sp. and Colletotrichum capsici colonies on Potato Dextrose Agar culture media. The results showed that Trichoderma sp. fungi can compete for space and resources against Colletotrichum capsici fungi macroscopically by controlling space and resources, and microscopically by producing antibiotics (antimicrobials) that can inhibit the growth of Colletotrichum capsici. The urgency of this research is the need for safe and environmentally friendly disease control efforts. One method that has been widely developed is by utilizing biological agents, such as Trichoderma sp. which is able to inhibit the growth of the pathogen Colletotrichum capsici.